2021
DOI: 10.3389/fcell.2021.698503
|View full text |Cite
|
Sign up to set email alerts
|

CD30-Positive Extracellular Vesicles Enable the Targeting of CD30-Negative DLBCL Cells by the CD30 Antibody-Drug Conjugate Brentuximab Vedotin

Abstract: CD30, a member of the TNF receptor superfamily, is selectively expressed on a subset of activated lymphocytes and on malignant cells of certain lymphomas, such as classical Hodgkin Lymphoma (cHL), where it activates critical bystander cells in the tumor microenvironment. Therefore, it is not surprising that the CD30 antibody-drug conjugate Brentuximab Vedotin (BV) represents a powerful, FDA-approved treatment option for CD30+ hematological malignancies. However, BV also exerts a strong anti-cancer efficacy in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 26 publications
(29 reference statements)
0
7
0
Order By: Relevance
“…CD30 is variably expressed in DLBCL, at a frequency of up to 60% depending on cut-off value [ 4 , 108 ], but unexpectedly, some studies have suggested that the response to brentuximab vedotin treatment does not correlate with CD30 expression [ 109 ]. This has led to a hypothesis that CD30-positive extracellular vesicles can transport brentuximab vedotin to CD30-negative tumor cells (a theory that is borne out by preclinical data) [ 109 ].…”
Section: Targeting Cd30 In Other Lymphomasmentioning
confidence: 99%
“…CD30 is variably expressed in DLBCL, at a frequency of up to 60% depending on cut-off value [ 4 , 108 ], but unexpectedly, some studies have suggested that the response to brentuximab vedotin treatment does not correlate with CD30 expression [ 109 ]. This has led to a hypothesis that CD30-positive extracellular vesicles can transport brentuximab vedotin to CD30-negative tumor cells (a theory that is borne out by preclinical data) [ 109 ].…”
Section: Targeting Cd30 In Other Lymphomasmentioning
confidence: 99%
“…Brentuximab vedotin can also affect CD30-antigen-negative cancer cells through bystander effects, although the extent of this is unknown. 7,25 Currently, BV is approved for patients with relapsed or refractory (R/R) Hodgkin lymphoma and CD30-positive anaplastic large cell lymphoma (Table 2). The drug is also approved for high-risk Hodgkin lymphoma treated with autologous stem cells and CD30-expressing myelofibrosis and cutaneous T-cell lymphoma (TCL).…”
Section: Brentuximab Vedotinmentioning
confidence: 99%
“…However, other factors in the tumor microenvironment may modulate response. 7,25 Another phase I trial evaluated the combination of BV and lenalidomide in the R/R DLBCL. 43 Of the enrolled 37 patients, 22 of the DLBCLs were negative for CD30.…”
Section: Diffuse Large B-cell Lymphomamentioning
confidence: 99%
See 1 more Smart Citation
“…However, as CD30 pos bystander cells are enriched in the tumor tissue in many cases of DLBCL, CD30 might be released within TME-derived EVs. Thus a model was proposed in which even in the absence of CD30 on the tumor cells, EVs can transport the targeting protein from cells of the TME to tumor cells ( 116 ). This model would explain the clinical efficacy of Brentuximab vedotin also in cases of lack of the targeting antigen on tumor cells.…”
Section: Disrupting the Ev “Remote Communication” To Improve Lymphoma Prognosismentioning
confidence: 99%